Evaluasi Ketercapaian Kompetensi Literasi Program Gerakan Literasi Sekolah: Faktor-Faktor yang Mempengaruhi - Parera, Aser; Yansa, Hajra; Jumrawati (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the achievement of basic literacy competencies of primary school students (SD/MI) and identify the factors that have the most influence on literacy completion. This study used a quantitative approach with the discriminant analysis method. The sample consisted of 90 students from grades 1 to 6 in Indramayu district, purposively selected based on variations in Indonesian language scores. The data collection instrument used Tactical Map 2.1 which measured students' abilities in reading, writing, and communication. Data were analyzed using Wilks' Lambda test and discriminant function coefficients to identify the dominant factor in differentiating literacy achievement. The results of the analysis showed the discriminant model was significant (Wilks' Lambda = 0.336; p < 0.001). The ability to write (0.736) and communicate (0.616) were the most dominant factors differentiating the completed and non-completed student groups, followed by reading (0.464). Meanwhile, age (0.047) and gender (0.214) had lower contributions. The findings suggest that strengthening literacy should include productive aspects, not just receptive, and encourage the transformation of holistic learning strategies in primary schools.